Velvet ants (Hymenoptera: Mutillidae) of the Algodones sand dunes of California, USA - Pitts, James P.; Wilson, Joseph S.; Williams, Kevin A.; Boehme, Nicole F. (Zootaxa, 2009)
The diversity of velvet ants (Hymenoptera: Mutillidae) on the Algodones Sand Dunes of southern California is investigated. Forty species are found to inhabit areas on and around the dunes. Sphaeropthalma django is described as a new species. Most of the species are known from males only. In an attempt to associate the sexes of the species, two internal transcribed spacers (ITS1 and ITS2) are sequenced for 11 female morphospecies of nocturnal Mutillidae found on the Algodones Sand Dunes. Their ITS sequences are compared to species known only from males that were also found on these same dunes. Sequences are compared for multiple individuals to assess genetic diversity. As has been found with other mutillids, intersexual sequence differences are much smaller than the interspecific differences. This work results in the matching of 11 females with their conspecific males using molecular data, including: Odontophotopsis arcuata, O. obscura, new comb., O. parva, O. villosa, Sphaeropthalma arota, S. blakeii, S. django, sp. nov., S. difficilis, S. ecarinata, S. militaris, and S. triangularis. Fresh females of O. inconspicua were unavailable, but an association of the female is made using morphological and distributional data. An Odontophotopsis female of unknown identity also is described, but not named. Sphaeropthalma helicaon (Fox), Photopsis lingulatus Viereck, Sphaeropthalma (Photopsis) carinata Schuster, Sphaeropthalma (Photopsis) helicaon coahuilae Schuster, Sphaeropthalma (Photopsis) helicaon diegueno Schuster are junior synonyms of Sphaeropthalma arota (Cresson). Mutilla hebes Melander is a junior synonym of Photomorphus clandestina (Viereck). Mutilla bellerophon Melander (nec Fox) and Mutilla (Photomorphus?) crepuscula Viereck are junior synonyms of Photomorphus bicolor (Blake). Odontophotopsis grata Schuster (nec Melander) is a junior synonym of O. acmaea Viereck. Neotypes are designated for O. obscura Schuster and O. quadrispinosa Schuster. Only Dasymutilla imperialis, D. nocturna and Sphaeropthalma django, sp. nov., were found to be restricted to the Algodones Sand Dunes. Odontophotopsis arcuata, O. parva, O. villosa and S. ecarinata are not restricted to the Algodones Sand Dunes, but can be found in much greater abundance on the dunes than elsewhere. Keys are provided for both sexes.